2018
DOI: 10.1016/j.marpol.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Occupational safety in aquaculture – Part 1: Injuries in Norway

Abstract: This article presents an overview of reported injuries in the Norwegian aquaculture industry focusing on the production of Atlantic salmon and trout, which dominates the fish farming industry in Norway. Two different data sets form the basis for the analysis: (i) occupational injuries reported to the Norwegian Labor and Welfare Administration, and (ii) serious occupational injuries reported to the Norwegian Labor Inspection Authority. The data sets on occupational injuries and serious injuries provide informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…In Norway, found that blows by objects, falls, entanglement or crush injuries, and pricks/cuts/punctures were the most common causes of injury, and open wounds, sprains, contusions, and fractures were the most frequently sustained injuries in Atlantic salmon net-pen culture from 2001 to 2014. 68 In a second report, Holen et al (2017) reported 34 fatalities in Norwegian aquaculture from 1982 to 2015, with most fatalities caused by loss of vessel (n = 15), man overboard (n = 5), and blow from an object (n = 6). 69 The authors suggested that seafaring vessel use and crane use represent critical intervention points for future worker safety interventions.…”
Section: Us Aquaculture Sectormentioning
confidence: 99%
“…In Norway, found that blows by objects, falls, entanglement or crush injuries, and pricks/cuts/punctures were the most common causes of injury, and open wounds, sprains, contusions, and fractures were the most frequently sustained injuries in Atlantic salmon net-pen culture from 2001 to 2014. 68 In a second report, Holen et al (2017) reported 34 fatalities in Norwegian aquaculture from 1982 to 2015, with most fatalities caused by loss of vessel (n = 15), man overboard (n = 5), and blow from an object (n = 6). 69 The authors suggested that seafaring vessel use and crane use represent critical intervention points for future worker safety interventions.…”
Section: Us Aquaculture Sectormentioning
confidence: 99%
“…The second and third highest frequency injuries were related to entanglements or crushes and falls, respectively. A unique risk was voltage-related injuries from exposure to static electricity released from plastic fodder tubes [46]. Mariculture is an emerging practice in the GoM, which involves shellfish farming but has the potential for expanding into deeper waters and different fisheries.…”
Section: Passive: * Stationary Capture or Culturementioning
confidence: 99%
“…Baker and Ferguson stated in 2006 that Australian fishers routinely work 24 to 96 h or more with little or no sleep [46]. A finding was that fatigue was responsible for 2% of human-related vessel collisions and 4% of groundings.…”
mentioning
confidence: 99%
“…These operations require work vessels with cranes, winches, and arrangements to secure the equipment that is undergoing maintenance. An analysis of serious injuries and fatalities shows that blows from an object, entanglements and crush, and man over board are the most common modes of injuries and causes for fatalities [5,48]. Equipment such as cranes, winches, the net cage, and work vessels, used in operations where subcontractors are involved, are often involved in these types of injuries.…”
Section: Steps 12 and 13 Identify Hazards And Develop Safety Requirementsmentioning
confidence: 99%
“…Employees are exposed to hazards through manual labor using sharp objects, such as hooks and knives. Serious injuries and fatalities have been reported in relation to operations using heavy machinery, such as cranes and winches [5]. In addition to the intrinsic challenges of working with such equipment, the forces from the environment constantly influence operations.…”
Section: Introductionmentioning
confidence: 99%